Active Vibration Control with Multi-Objective Control Output for Typical Engineering Equipment - JIAN, Xu; TONG-YI, Zhang; WEI, Huang; MING-YI, Hu (Engineering Transactions, 2017)
In traditional active vibration control, a single-objective control output is often considered and constrained, but in fact some conflicting performance indexes are always emerging simultaneously and a one-sided method for pursuing only one excellent output is adopted, which may sacrifice other control characteristics. In this paper, a novel active vibration control with multi-objective control output was proposed for machinery equipment and sensitive equipment, and the latest artificial intelligence – multi-objective particle swarm optimization (MOPSO) was utilized, and the active controller was evaluated by the H_∞ criterion, meanwhile an active control with a single-objective control output was also carried out for comparison. Numerical studies demonstrated that a pair of conflicting indexes could be balanced well in the proposed strategy, and thus only one blindly pursued control output was effectively overcome.